A Case of Lenvatinib-Induced Focal Segmental Glomerulosclerosis (FSGS) in Metastatic Medullary Thyroid Cancer - Kathryn Fleming; James McGuinness; David Kipgen; Hilary Glen; Pavlina Spiliopoulou (Case Reports in Oncological Medicine)
We describe a case of lenvatinib (E7080) associated focal segmental glomerulosclerosis (FSGS) encountered during the treatment of metastatic medullary thyroid cancer. Proteinuria is a relatively common side effect of VEGF-targeted treatments and can occasionally result in treatment discontinuation. Here, we describe a patient who developed secondary FSGS necessitating discontinuation of treatment at first but who was subsequently rechallenged with anti-VEGF-targeted treatment without recurrence of proteinuria. Lenvatinib was a novel experimental agent at the time the treatment took place; however, its recent licensing for the treatment of thyroid malignancies in the UK makes reporting of these adverse effects all the more important now.